A Note on 7Q19, a Greek Fragment of Jubilees from Qumran? - Magnelli, Adalberto; Petrantoni, Giuseppe (Anabasis. Studia Classica et Orientalia, 2017)
A Greek text written on a broken papyrus impression from Qumran (Cave 7) initially was identified with a possible Pauline epistle. But, the words κτίσεως, referring to a sort of “creation, foundation”, and ταῖς γραφαῖς, probably relating to the Holy Scriptures, give us a possible evidence that the whole inscription could refer to a Parabiblical or Pseudoepigraphical text. In fact, a comparison between the Greek fragment 7Q19 from Qumran and the reconstructed Hebrew version of Jubilees 1:29 could show that probably 7Q19 is the first known Greek fragment of a lost Pseudoepigraphical Book of Jubilees.